2016
DOI: 10.1007/s10493-016-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Esterase mediated resistance in deltamethrin resistant reference tick colony of Rhipicephalus (Boophilus) microplus

Abstract: Monitoring of acaricide resistance is considered as one of the important facets of integrated tick management. In an attempt of development of resistance monitoring indicators, in the present study two reference tick lines of Rhipicephalus (Boophilus) microplus maintained in the Entomology laboratory, Indian Veterinary Research Institute (IVRI), Izatnagar, India, were studied to determine the possible contributing factors involved in development of resistance to deltamethrin. Electrophoretic profiling of ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Chlorpyrifos‐treated ticks, on the other hand, showed a significant decrease in GSH, an increase in MDA and a significant inhibition in AchE. Gupta et al (2016) reported an inhibition in AchE in R. microplus ticks treated with deltamethrin, and they ascribed the ticks' resistance to deltamethrin to this inhibition. AchE is also suppressed in the chlorpyrifos‐treated ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorpyrifos‐treated ticks, on the other hand, showed a significant decrease in GSH, an increase in MDA and a significant inhibition in AchE. Gupta et al (2016) reported an inhibition in AchE in R. microplus ticks treated with deltamethrin, and they ascribed the ticks' resistance to deltamethrin to this inhibition. AchE is also suppressed in the chlorpyrifos‐treated ticks.…”
Section: Discussionmentioning
confidence: 99%
“…It also exhibits anticholinesterase activity [26,27]. Current research on AchE in ticks mainly focuses on resistance to commercial insecticides and essential oils derived from plants [28,29,30,31]. Our study identi ed four AchEs in one tick species and demonstrated that HL-AchEs were signi cantly in uenced by cinnamaldehyde stimulation.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, overexpression of esterases and Glutathione S-transferases is associated with metabolic detoxification of pesticides (Bellgard et al, 2012). In ticks, these enzymes have been implicated in resistance through the metabolic detoxification mechanism (Bellgard et al, 2012;Nandi et al, 2015;Ghosh et al, 2015;Gupta et al, 2016;Ghosh et al, 2017;Chigure et al, 2018;Fular et al, 2018). Regarding esterases, CaE catalyze the hydrolysis of esters and are classified in the serine hydrolase superfamily, involved in detoxification and playing an important physiological role in lipid metabolism (Ran et al, 2009).…”
Section: Discussionmentioning
confidence: 99%